Social Media Marketing Dynamics and Brand Loyalty: A Sequential Mediation Model in the Indonesian Packaged Drinking Water Industry - Andika, Andika; Yusrita, Yusrita; Nugroho, Joko Purwanto; Luthfiana, Della Nanda; Hak, Rizki Zaenul (Jurnal Siasat Bisnis, 2024)
Purpose – This study uses the stimulus organism response (SOR) as the theory framework to analyze the sequential mediating roles of brand experience (BE), brand trust (BT), and brand love (BLV) to show the connection between Social Media Marketing (SMM) activities and brand loyalty (BL). Design/methodology/approach – The study approach was empirically evaluated using 310 SM users as data who follow bottled water brands on any platform and have made a purchase. Furthermore, a sequential multiple mediation model was tested using PLS-SEM. Findings – The results indicate that SMM significantly impacts BE, and BE significantly affects BT and BLV. Subsequently, this influence of BT and BLV contributes to an increase in BL. Additionally, it was revealed that BE, BT, and BLV sequentially and significantly mediate the relationship between SMM and BL. Research limitations/implications – Its cross-sectional design, sample bias towards younger, educated respondents, a narrow focus on BL from SMM activities, and a lack of consideration for sustainability and broader product types suggest a need for more diverse and longitudinal future research. Practical implications – The result emphasizes the need for brands to leverage SM as a critical channel for consumer engagement, suggesting the adoption of personalized, entertaining, and interactive digital campaigns to increase through memorable BE. Originality/value – This study pioneers using SOR theory to explore the SMM impact on BL within the bottled water industry, providing novel insights through empirically validating a model that links SMM activities with loyalty via BE, BT, and BLV.